Why nations fail [compact disc, unabridged] : the origins of power, prosperity and poverty - Acemoglu, Daron (Random House Audio : Books on Tape, 2012)
Why are some nations more prosperous than others? "Why Nations Fail" sets out to answer this question, with a compelling and elegantly argued new theory: that it is not down to climate, geography or culture, but because of institutions. Drawing from an extraordinary range of contemporary and historical examples, academics Acemoglu and Robinson argue that nations can only prosper if the people are allowed to keep the wealth that they earn.